SCIENTIFIC FOUNDATIONS OF POLITICAL EXTREMISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article describes the scientific foundations of political extremism. The etymology of political extremism, the emphasis is on the diversity of its various manifestations and features. The founders of the concept of political extremism are given a place in their scientific views and hypotheses. An analysis of the diversity and specificity of scientific views on this phenomenon will be conducted and it will be said that only new research is being conducted by scientists. The expression political terrorism has now moved away from the classical etymological characteristic and has been considered as evolving in accordance with the requirements of the time, adapted according to the moment. But the theoretical scroll tells us that there are many similarities, many similarities.
Keywords: political extremism, terrorism, globalization, transformation, political culture, political process, religious extremism, conflicts, inequality, fascism, Bolshevism, conflict, radicalism, extremist opposition, and anti-liberalism